Regulatory Gaps in Addressing Cyber Begging in Indonesia A Criminal Policy Perspective - Maulana Dahlan; Yuliati; Faizin Sulistio (PT ARRUS Intelektual Indonesia, 2026)
The rapid advancement of information and communication technology has given rise to cyber begging, a phenomenon whereby individuals exploit digital platforms to solicit financial assistance from the public, often through systematic manipulation of digital empathy. This study aims to analyze the regulatory gaps within Indonesia's criminal law system concerning cyber begging practices and to formulate an ideal criminal policy response. Employing normative legal research through statute, conceptual, and comparative approaches, this study finds that Indonesia's National Criminal Code (Law No. 1/2023) and the Electronic Information and Transactions Law (Law No. 1/2024) fail to comprehensively address the characteristics of cyber begging based on digital empathy exploitation. The essence of cyber begging as a legal problem lies in four core elements: narrative manipulation, empathy exploitation, information asymmetry, and systematic economic orientation. This study proposes a multi-layered regulation model integrating preventive, administrative, and selective penal approaches grounded in the ultimum remedium principle. Criminalization should be restricted to cyber begging involving information manipulation, exploitation of vulnerable groups, and use of false identities, while honest and transparent solicitation of assistance should remain outside the scope of criminal law.